2014
DOI: 10.1002/jcb.24792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Regulation of Human Osteoclast Differentiation

Abstract: Human skeletal aging is characterized as a gradual loss of bone mass due to an excess of bone resorption not balanced by new bone formation. Using human marrow cells, we tested the hypothesis that there is an age-dependent increase in osteoclastogenesis due to intrinsic changes in regulatory factors [macrophage-colony stimulating factor (M-CSF), receptor activator of NF-κB ligand (RANKL), and osteoprotegerin (OPG)] and their receptors [c-fms and RANK]. In bone marrow cells (BMCs), c-fms (r=0.61, p=0.006) and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 46 publications
1
59
0
3
Order By: Relevance
“…The RANKL/OPG ratio is an indicator of regulation of osteoclast differentiation . For example, we found that the RANKL/OPG ratio in marrow stromal cells (MSCs) increased with the age of the study subject and was correlated with spontaneous in vitro generation of osteoclasts from marrow . In addition, the RANKL/OPG ratio from subjects receiving alendronate was half that for control subjects, and in vitro treatment of MSCs with alendronate reduced the RANKL/OPG ratio in a dose‐dependent manner .…”
Section: Discussionmentioning
confidence: 98%
“…The RANKL/OPG ratio is an indicator of regulation of osteoclast differentiation . For example, we found that the RANKL/OPG ratio in marrow stromal cells (MSCs) increased with the age of the study subject and was correlated with spontaneous in vitro generation of osteoclasts from marrow . In addition, the RANKL/OPG ratio from subjects receiving alendronate was half that for control subjects, and in vitro treatment of MSCs with alendronate reduced the RANKL/OPG ratio in a dose‐dependent manner .…”
Section: Discussionmentioning
confidence: 98%
“…Loss of bone mass associated with human skeletal aging can be explained in part by the age-related decline in in vitro osteoblast differentiation [1013,24] and by the age-related increase in in vitro osteoclast differentiation [64] with bone cell progenitors from bone marrow. Finding vitamin D-hydroxylases and regulated activity in hMSCs provides support for the hypothesis of an autocrine/paracrine role of vitamin D metabolism in human osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal homeostasis depends on multiple factors regulating bone remodeling, the cycle that consists of bone resorption by osteoclasts and new bone formation by osteoblasts. Emerging evidence from in vitro studies with human marrow stromal cells from young and old subjects shows an age-related decline in osteoblast differentiation potential in vitro [1, 2] and an age-related increase in ability to support osteoclastogenesis in vitro [3]. Little is known about the effects of age on in vitro hematopoiesis.…”
mentioning
confidence: 99%